2019
DOI: 10.5125/jkaoms.2019.45.6.369
|View full text |Cite
|
Sign up to set email alerts
|

Vestibuloplasty covering titanium mesh with grafted free gingiva on anterior mandible: technical report and rationale

Abstract: J Korean Assoc Oral Maxillofac Surg 2019;45:369-373) This paper describes a patient with an insufficient vestibular depth for a removable partial denture who underwent vestibuloplasty with a free gingival graft using a titanium mesh in the anterior mandible. Free gingiva was harvested from the palatal mucosa, and a partial thickness flap was elevated at the recipient site. After minimal suturing for the graft, a titanium mesh was fixed over the graft. The mesh was removed four weeks after surgery. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The surgical procedure was performed as the described in a previous report 6 . A horizontal incision was made at the mucogingival junction of the recipient site in patient #1 ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical procedure was performed as the described in a previous report 6 . A horizontal incision was made at the mucogingival junction of the recipient site in patient #1 ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, when used with grafts, the sufficient rigidity of titanium mesh is expected to reduce dead space by exerting constant pressure over the graft. An approach to vestibuloplasty using titanium mesh and FGG was reported for the edentulous anterior mandible 6 . The titanium mesh used for this technique was flexible enough to provide even pressure across the graft to prevent dead space, minimize the need for stitches, and reduce operation time 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] In order to obtain a satisfactory denture-bearing area, lower anterior ridges with insufficient quality and quantity can undergo different types of procedures such as implant placement and vestibuloplasty. [ 2 3 ] It has been shown that dental implants can not only provide appropriate stability and convenience but can relatively prevent alveolar bone resorption as well. [ 4 5 6 7 ] However, in addition to prohibitive cost and difficulties in providing the necessary hygiene, implant placement is contraindicated in patients with epilepsy, diabetes, endocarditis, osteoradionecrosis, cardiac transplant, myocardial infarction, immunosuppressive disorders, active treatment of malignancies, and drug abuse.…”
Section: Introductionmentioning
confidence: 99%